Analisis Kemampuan Putaran Bolak-Balik Roller Mixer Stastis dengan Setting Buzzer Pengingat Waktu - Yudithia, Frenzi Agres; Herda, Deri Latika; Rossa, Anindita Aulia (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2023)
Roller mixer is a laboratory tool to assist the process of homogenization in blood hematology examination. Generally, this tool works by rotating the rollers which mix the blood sample and anticoagulant agent. Apart from that, this mixer roller wobbles when it is running, while rotating in the same direction following a predetermined speed setting. In this research a static roller mixer prototype has been made, which can rotate back and forth with a pause setting every 30 seconds. So that the prototype can be used as a supporting tool in the laboratory, several test times are carried out for 1-15 minutes. Analysis of the ability to rotate back and forth the prototype was also carried out at different speed levels, namely 33 RPM, 40 RPM, 50 RPM, and 60 RPM. The results of the tests that have been carried out show that the prototype has a stable rotational speed of 31.5 seconds. The measurement has a time difference of 5% against the setting time. Based on the data it can be concluded that the increase in the roller speed level does not affect the change in the time test value that has been carried out.